AKTIVITAS ANTAGONISTIK KAPANG ENDOFIT DUWET (Syzygium cumini (L.) Skeels) TERHADAP Alternaria porri PENYEBAB BERCAK UNGU PADA BAWANG MERAH (Allium ascalonicum L.) SECARA IN-VITRO - Ristia Rachmatunnisa; MG. Isworo Rukmi; Sri pujiyanto (Jurnal Akademika Biologi, 2017)
Endophytic fungi has been capable in producing secondary metabolites similar to those produced by its host. Secondary metabolites in some parts of duwet tree showed an antifungal activity. The aims of this study were to determine the ability of duwet endophytic fungi in inhibiting A. porri fungus, a pathogenic agent for  purple blotch disease on onion. The experiment conducted using CRD with eight endophytic fungi isolates as treatment with three replications. Antagonistic activity observed using dual culture method. The endophytic fungal isolates were conventionally identified to genus level. The results showed that endophytic fungi were identified as five isolates of Penicillium and one isolate of Aspergillus, Fusarium and mycelia sterilia. The antagonistic acitivity of duwet endophytic fungi against A. porri were varied between 18.1% - 47.3%. The highest antagonistic activity showed by Fusarium JD1 (47,3%). Keywords: Alternaria porri, purple blotch, onion disease, antagonistic fungi, endophytic fungi.